Sociological theory - Ritzer,George (The McGrraw-hill companies, 1996)
This work spans the history of sociological theory from its inception to the present. Divided into four parts it covers early sociological thinkers, each major school, recent integrative developments, and contemporary theories of modernity, structuralism and post-structuralism.